Do Pharmacists know which patients with bowel syptoms should seek further medical advice? A survey of Pharmacists practicing in community pharmacy in Western Australia - Jiwa, Moyez; Spilsbury, Katrina; Duke, Janine (Harvey Whitney Books, 2010)
Background: Pharmacists in Australia are routinely asked to advise people with lower bowel symptoms. Clinical, demographic, and working environment parameters may affect whether appropriate referral for advanced care is advised by pharmacists. Objective: To characterize how selected clinical, demographic, and working environment variables affect the likelihood of a pharmacist providing a referral for patients with lower bowel symptoms to consult a general practitioner, and to investigate factors associated with agreement with an expert panel and colorectal cancer guidelines. Methods: Self-administered questionnaires were distributed to a random sample of 300 pharmacists in Western Australia. Vignettes were constructed around 6 clinical variables and pharmacists were asked to describe a referral pathway. Logistic regression was used to identify factors associated with odds of referral and agreement with an expert panel.Results: One hundred sixty-seven completed surveys were returned, giving a response rate of 56%. The odds of referral to a general practitioner were mostly associated with presenting symptoms, although lower odds of referral were observed with increasing volumes of weekly prescriptions. The odds of pharmacists agreeing with the expert panel for an urgent referral were 70% (95% CI 50 to 80) lower for weight loss as the presenting symptom compared to rectal bleeding. The expert panel considered weight loss or rectal bleeding of 4 weeks' duration as meriting an urgent referral, but 63% and 30% of pharmacists respectively, disagreed. In contrast to cancer guidelines, over 60% of respondents did not consider persistent diarrhea in a 65-year-old patient as a likely symptom of significant bowel pathology. Conclusions: In general, pharmacists' patterns of referral were influenced by clinical symptoms and not by demographic or working environment variables. They over-referred patients with diarrhea but under-referred those with weight loss and rectal bleeding, according to the expert panel. This is a cause for concern because any unexplained rectal bleeding should be referred for further investigation.